Studying the Effects of Responsible Financial Practices of a Fintech on Sustainable Financial Inclusion - Tuhin Siddharth; Rohit Kumar (The Bioscan, 2024)
Objectives: This paper studies the impact of attitude towards fintech adoption on sustainable financial inclusion of a population in the extended TAM model. Methods: The study uses the technology acceptance model, or TAM, for examining the impact of independent variable on the sustainable financial inclusion. Judgmental sampling technique is used for data collection using a structured self-administered questionnaire based on five-point Likert scale. The data collected is then statistically analyzed using SPSS and AMOS software. Findings: The results reveal that the independent variables, perceived usefulness, perceived ease of use and responsible financial practices have a positive impact on the attitude towards fintech adoption, which in turn has a significant positive impact on sustainable financial inclusion. These findings shall be helpful in policy and strategy formulation of the government and fintech firms in accordance to united nations sustainable development goals and world bank financial inclusion initiatives. Novelty: The study uses primary data collection, based on self-developed research model after studying the available existing literature on the subject and then analyses it to come to conclusion. The work is novel.